Overview of digital asset and its process under the inheritance management - Drs Nasrul, Muhammad Amrullah; Mohd Alam Shah, Nurin Athirah; Muhamad Ibrahim, Najhan; Abdul Manaf, Zati Ilham (Asian Scholars Network, 2023)
Generally, after the deceased died, there is a process of inheritance management where both movable and immovable assets are distributed to the respective heirs. This process has been practiced by all levels of society despite their race and religion. However, recently, assets in Malaysia began to experience modernization where people started to invest in digital asset. Although Malaysia’s digital asset laws are still in their infancy, it indirectly raises issues for the inheritance management about the status of the digital asset if it is left by the deceased especially for the Muslims. In addition, with cash in banks, investments in unit trusts, Amanah Saham Berhad (ASB), Tabung Haji and automobiles, digital assets are currently a prominent topic in the inheritance management debate. Many people are unsure whether digital assets qualify as deceased person's assets or not and its status in Islam. Hence, the purpose of this study is to examine the development of digital asset and its status in inheritance management. In this study, the researcher employs a qualitative approach, by conducting library-based research on the relevant materials including, but not limited to statutory provisions, case laws, textbooks, journal articles, newspapers, conference proceedings, and seminar papers. Based on the findings, it is permissible to conduct inheritance management using digital asset but subject to certain conditions.